The Pengaruh Model Project Based Learning terhadap Kemampuan Berpikir Kritis Siswa Kelas IV dalam Pembelajaran IPAS - Sukmawati; Ajwar, Muhamad; Hairunisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The goal of this study is to find out how the Project Based Learning (PjBL) model influences the critical thinking skills of students at SDN 55 Bima City who are studying the Natural and Social Sciences (IPAS). The study is based on the fact that IPAS students don't think critically enough because the lecture technique is so common. The study uses a pretest-posttest control group quasi-experimental design and a quantitative technique. There are two classes in the sample: class IV A, which was taught using the PjBL model as an experimental group, and class IV B, which was taught in a traditional way as a control group. We employed essay examinations and observation sheets based on Facione's critical thinking indicators to get the information. The study of the data showed that the experimental group's scores went up by 18.1 points, whereas the control group's scores only went up by 7.1 points. The t-test's significance value of 0.000 (<0.05) shows that there is a big difference between the two groups. Students in the experimental group not only did better on tests, but they also took part in project activities including solving problems, working together, and debating. These results show that PjBL is a good way to help students learn in a way that is meaningful and relevant to their lives, as well as to improve their critical thinking skills. The PjBL model is offered as a replacement for traditional science lessons in elementary schools to make it easier for schools to use the Independent Curriculum